PERAN RUANG PUBLIK SEBAGAI TEMPAT INTERAKSI MANUSIA DAN LINGKUNGAN DI PERKOTAAN - Defia Aini Rindu; Ahmad Faisal Imadudin; Aulia Agnesia Caroline; Didik Tri Setiyoko (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Urban public spaces serve as fundamental elements in facilitating human-environment interaction within cities. This study aims to identify and analyze the functions of public spaces in supporting social, ecological, and educational interactions, the types of activities occurring, and their significance for urban communities. Employing a qualitative literature review approach, this research synthesizes relevant academic sources from 2019 to 2025 retrieved from Google Scholar, Scopus, and JSTOR. The population consists of academic literature concerning urban public space functions and interactions, with purposive sampling selecting the most pertinent and credible works. Data were analyzed thematically to reveal key patterns in social use, environmental impact, and educational roles. The results show that urban public spaces perform multifunctional roles by fostering social cohesion, enhancing environmental sustainability through green areas and community participation, and serving as informal educational platforms. The study concludes that well-designed, participatory public spaces improve quality of life and support sustainable, inclusive urban development. Future research should include empirical studies to deepen practical understanding and further explore participative design models. These findings have practical implications for urban planners, public space managers, and community stakeholders to integrate social, ecological, and educational dimensions effectively.